Does Switching Cost Affect Dual Rural Banks Market Power? - Fajri, Moh Najikhul; Purwono, Rudi (Universitas Airlangga, 2022)
This study aims to review the effect of switching costs on rural bank market power. This study is using dynamic panel regression of the Generalized Method of Moments (GMM). This paper used panels of 1266 rural banks and 113 Sharia Rural banks from 2013 to 2019. To further analyze this study using Lerner Index as proxies of market power, Bertrand Competitions models as proxies of switching costs, and banking indicators covering bank size, equity, non-interest income, and the burden of allowance for productive assets (Lost Loans Provision). The results show that switching costs have a significant positive effect on the conventional rural bank and negatively affect sharia rural bank's market power. This condition is caused by various reasons, namely the limited choice of rural banks so that consumers survive the switching costs charged. Meanwhile, in sharia rural bank transparency is clearly seen on the side of mudharobah and musyarakah which makes it unable to increase financing margins freely.